Generation of electromagnetic waves in the terahertz frequency range by optical rectification of a Gaussian laser pulse in a plasma in presence of an externally applied static electric field. Issue 6 (6th July 2017) - Singh, Ram Kishor; Kumar, Subodh; Sharma, R.P.
Abstract : We propose a theoretical model for the generation of electromagnetic waves in the terahertz (THz) frequency range by the optical rectification of a Gaussian laser pulse in a plasma with an applied static electric field transverse to the direction of propagation. A Gaussian laser pulse can exert a transverse component of the quasi‐static ponderomotive force on the electrons at a frequency in the THz range by a suitable choice of the laser pulse width. This nonlinear force is responsible for the density oscillation. The coupling of this oscillation with the drift velocity acquired by electrons due to the applied static electric field leads to the generation of a nonlinear current density. A spatial Gaussian intensity profile of the laser beam enhances the generated THz yield by many folds as compared to a uniform spatial intensity profile.